Wave simulators as a means of preventing covid-19 - Mikhailov, N.G.; Lubyshev, PhD E.A.; Agashin, M.F.; Kavokin, A.I. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to scientific substantiation of physical culture means for the prevention of the incidence of covid-19 in children and youth. Methods and structure of the study. The experiment involved children aged six to ten who attended elementary school and kindergarten No. 1604. Pedagogical impact was aimed at identifying the results of classes with wave simulators. Indicators of pulse, arterial pressure, physical development and physical fitness were determined. Results and conclusions. As the study showed, physical activity with children aged 6-10 years using wave simulators has a positive effect on hemodynamics, which is expressed in a significant (p<0.05) decrease in heart rate and systolic pressure at rest, within the age norm; unreliable increase in indicators of physical development (p>0.05); a significant increase in the development of physical qualities (p<0.05). The results of the study testify to the health-improving effect of training with wave simulators, the economization of the indicators of the cardiovascular system, as well as the development of the basic physical qualities of children from 6 to 10 years old.